Insight into Various Casting Material Selections in Rapid Investment Casting for Making EDM Electrodes - Thanh Tan Nguyen; Van-Thuc Nguyen; Van Tron Tran; Anh Thi Le; Thanh Duy Nguyen; Quoc Dung Huynh; Minh Tri Ho; Minh Phung Dang; Hieu Giang Le; Van Thanh Tien Nguyen (Micromachines)
Investment casting is a precision casting technology that can produce complex shapes from various materials, particularly difficult-to-cast and difficult-to-machine metallic alloys. Meanwhile, electrical discharge machining (EDM) is a well-known technique for producing ultra-precise mechanical parts, and electrode quality is crucial. Few studies have explored how rapid prototyping (RP) pattern generation and investment casting influence the final product’s shape, dimensions, and surface roughness. This study investigates EDM electrode fabrication using investment casting and RP-generated epoxy resin patterns. We examine the effects of electrode materials (CuZn5, CuZn30, and FeCr24) on surface roughness, alongside the impact of ceramic shell thickness and RP pattern shrinkage on electrode quality. The EDM electrodes have a shrinkage of 0.8–1.9% and a surface roughness of 3.20–6.35 μm, depending on the material selections. Additionally, the probability of shell cracking decreases with increasing shell thickness, achieving stability at 16.00 mm. This research also applies investment casting electrodes to process DC53 steel. The results indicate that the surface roughness of the workpiece after EDM machining with different electrode materials is in the range of 4.71 µm to 9.88 µm. The result expands the use of investment casting in electrode fabrication, enabling the production of high-precision electrodes with complex profiles and challenging materials, potentially reducing both time and cost.